Advertising: on the advertiser's Mind - Macera, Danilo (2020)
Edward Bernays is, undoubtedly, the most significant figure in the field of propaganda, and an inescapable reference when researching or discussing this topic. This article seeks to show the most important ideas, of this extraordinary thinker, of his book "Propaganda" of 1927, in addition to analyzing them in terms facts, strategies and characters of the past, and present history, such as Brexit, Kellogg Co., UEFA, Joseph Goebbels, Purina Dog Chow, among others, with the purpose of validating the validity, impact and significance of a visionary's thought, after close to a century.